2020
DOI: 10.1007/s42241-020-0032-2
|View full text |Cite
|
Sign up to set email alerts
|

A review on flow-induced vibration of offshore circular cylinders

Abstract: As a fundamental fluid-structure interaction (FSI) phenomenon, vortex-induced vibrations (VIVs) of circular cylinders have been the center of the FSI research in the past several decades. Apart from its scientific significance in rich physics, VIVs are paid great attentions by offshore engineers, as they are encountered in many ocean engineering applications. Recently, with the development of research and application, wake-induced vibration (WIV) for multiple cylinders and galloping for VIV suppression attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(25 citation statements)
references
References 168 publications
(262 reference statements)
0
15
0
Order By: Relevance
“…In the present experimental setup, the radius of the cylinder's rotation was kept constant (Table 1). Previous studies on FIV have reported the significance of two-dimensionality of the motion comprising the cross-flow and in-line components (e.g., [19,20]). The rotational motion generally involves both components; therefore, a radius of the cylinder's rotation that gives rise to a two-dimensional FIV to the maximum extent, may enable an increase in the available energy.…”
Section: Mechanical Interpretationmentioning
confidence: 99%
“…In the present experimental setup, the radius of the cylinder's rotation was kept constant (Table 1). Previous studies on FIV have reported the significance of two-dimensionality of the motion comprising the cross-flow and in-line components (e.g., [19,20]). The rotational motion generally involves both components; therefore, a radius of the cylinder's rotation that gives rise to a two-dimensional FIV to the maximum extent, may enable an increase in the available energy.…”
Section: Mechanical Interpretationmentioning
confidence: 99%
“…This research area has received much attention in recent decades. [6][7][8][9][10][11] Furthermore, studies dedicated to the flow around 3D geometries arising from spanwise inhomogeneity, truncated cylinders and presence of wall have formed another realm of research.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the fluid-structure interaction (FSI) problem of cylinders open to the uniform flow [1] that has been widely investigated, cylinders relative to oscillatory flow has attracted less attention. However, its significance cannot be undermined for its rich physics as well as its existence in all kinds of engineering projects, especially in the ocean engineering field.…”
Section: Introductionmentioning
confidence: 99%